Assessing articulatory perturbations during a sung vowel-matching exercise using articulography. (May 2021) - Daffern, Helena; Gully, Amelia Jane
Abstract: Vowel matching is considered a beneficial acoustic strategy for 'choral blend', but little is known about the articulatory changes that occur in practice. This paper explores the use of electromagnetic articulography (EMA) to examine the articulatory modifications used by singers when asked to blend with a unison singing voice. Five choir singers were recorded sustaining vowels with EMA electrodes placed on the tongue and the lips. During this task, subjects were asked to blend to a pre-recorded stimulus (same pitch and vowel). In a control condition no stimulus was played. Vowels /ɑ, i, u/ at pitches D4, F#4 and A4 were presented in each condition in a randomised order. Fundamental frequency (fo ), intensity and the first three formant frequencies were estimated from the acoustic signal and analysed alongside the synchronous EMA data. Baseline and matching conditions were compared for each recording. All subjects significantly shifted their fo in one matching condition suggesting that tuning might be their primary blending strategy. Significant differences in multiple sensor movements were only observed for the professional subject. Analysis of the trajectories of these sensor movements suggests a delay in response similar to expectation from tuning literature. EMA is shown to be a promising tool to investigate articulatory movements in addition to acoustic features of singers when blending their voice to another. These protocols will be valuable for understanding relationships between articulatory and acoustic features as voices adapt to external stimuli, which is especially applicable for vocal training and choral pedagogy.